Potential of kenaf and coir fibers as thermal insulators / 'Aamirah Azme and Nurul Edora Abdul Rahim - Azme, 'Aamirah; Abdul Rahim, Nurul Edora (Faculty of Applied Sciences, 2015)
This study was done to investigate potential of using kenaf and coir fibers as thermal insulators. Different fiber ratio of 100%) kenaf, 100% coir, 75% kenaf 25% coir and 25% kenaf 75% coir were used in creating the insulators walls. The thermal conductivity of each fiber was recorded for every 10 minutes. Thermal insulating capabilities were observed based on the change in temperature. The model buildings were exposed under the sunlight for 8 hours. From the results, it was found that denser materials have higher thermal conductivity and therefore are poor insulators, whereas the lightweight materials have lower thermal conductivity and considered as better thermal insulators. The 75% kenaf 25% coir of treated fiber was founded to be the best combination as thermal insulators. Meanwhile, 100% untreated kenaf fiber was known as the best fiber for making thermal insulator.